Projeto MinerH: investigação do impacto dos critérios de alocação de rins de doadores falecidos na lista de espera por transplante - Bonome, Karoline da Silva [UNIFESP] (2018)
Introduction: The Brazilian National Transplant System (SNT), which deals with organ sharing and management of transplant activities, is recognized as a successful policy. Regarding kidney transplants, Brazil reaches the top positions in international rankings of absolute numbers of transplants performed, showing significant rates of graft and patient survival. The allocation of deceased donor kidneys is based on the principles of equity (equal access to the organs for all), utility (maximizing the benefits after the transplant) and transparency. Rules that focus on efficiency might be disfavoring equity, though there are alternatives to correct this distortion. In other countries the allocation schemes have been frequently evaluated to provide evidences to discuss its impacts and refining the rules to achieve a balance between equity and utility. Objective: This project, unprecedented in Brazil, aims to describe the impacts of the current allocation rules on the equity of kidney transplant process establishing different groups among waitlisted recipients. Methods: Cluster analysis associated with multinomial logistic regression models were used to assess the effects of the main factors involved in kidney allocation. The database includes 17,752 recipients and 4,808 donors from Histocompatibility Laboratory of Immunogenetics Institute of the Association for Research Incentive Fund (IGENAFIP), Region I, São Paulo registered between January 1, 2005 and December 31, 2015. Results: Recipients were clustered in seven distinct groups (two nonselected recipient groups and five selected recipient groups). Multinomial logistic regression adjusted for blood group, sensitization level and HLADR and HLAB category reveals higher risks of being part of worse groups for homozygous, highly sensitized and blood group O patients, for example. Conclusion: This study uncovers the real effects of kidney allocation criteria in Brazil, addressing inequities among different recipient profiles. Factors such as HLA rareness/homozygosity and sensitization were associated with longer waiting times and lower selection rates. More studies on other databases are necessary to firmly verify these effects and so improve Brazilian allocation scheme to achieve a balance between equity and utility.